Antioxidant Nanomaterial Based on Core–Shell Silica Nanospheres with Surface-Bound Caffeic Acid: A Promising Vehicle for Oxidation-Sensitive Drugs - Arriagada, Francisco (Nanomaterials (Basel), 2019)
The design of efficient, biocompatible, and easily prepared vehicles for drug delivery is a subject of great interest for medicine and pharmaceutical sciences. To achieve the above goals, surface functionalization is critical. Here, we report a hybrid nanocarrier consisting of core–shell silica nanospheres and the antioxidant caffeic acid linked to the surface, to evaluate their in vitro antioxidant capacity, their capability to protect oxidation-sensitive compounds incorporated in nanoparticles, and to study the interaction with bovine serum albumin protein. The results show that the radical-scavenging activity of immobilized caffeic acid is attenuated in the silica nanospheres; however, other antioxidant properties such as Fe(2+)-chelating activity and singlet oxygen quenching are enhanced. In addition, caffeic acid is protected from binding to proteins by the nanoparticle, suggesting that this nanosystem is more likely to maintain the antioxidant activity of caffeic acid in biological media. Finally, the natural antioxidant barrier on the nanocarrier is able to delay the degradation of a compound incorporated into this nanovehicle. Considering all findings, this work proposes a suitable tool for pharmaceutical and cosmetic industries as an antioxidant nanocarrier for oxidation-sensitive drugs.